A Unique Case of Muscle-Invasive Metastatic Breast Cancer Mimicking Myositis. (28th June 2017) - Gyorffy, Janelle; Philbrick, Samuel M.; Bersabe, Adrian R.; Upton, Richard J.; Mathis, Derek A.; Peters, Austin; Brown, Alexander
Abstract : Breast cancer rarely metastasizes to the muscles, and it is even more unusual for this phenomenon to result in airway compromise. We present a unique case of an 84-year-old female who presented with neck swelling and upper airway obstruction due to metastatic breast cancer invading the sternocleidomastoid muscles. After establishing the diagnosis and discussing possible treatment options, the patient elected for antiestrogen therapy, palliative tracheostomy, radiation therapy, and hospice services.